DANA PUNIA DALAM TRADISI MASURYAK - Tary Puspa, Ida Ayu (PANGKAJA, 2012)
Tradition is integrated in the implementation of other forms of religious ceremonies in Baliimplemented as a legacy for generations. Likewise masuryak traditions are still carried out by the Hindu community in the villageof Tabanan Bongan. The tradition is still carried out to date to coincide with the feast of Brass. Feast day which falls after ten days of Galungan and just in the local community Tumpek interpreted as a return of their ancestors to heaven. To deliver these ancestors made a ritual and equipped with money being thrown into the air accompanied by the cheering (masuryak). The money will be taken by his family, relatives, community, and even from outside the village were there to enjoy the windfall. This form berdanapunia way the focus of religion in this time era. Keywords: punia funds, tradition masuryak